Implementation of Finite State Machine in Flowchart-Based Visual Programming Game - Iqbal Al Mahdi; Saiful Bukhori; Muhammad Ariful Furqon (Bina Nusantara University, 2025)
This study explores the implementation of Finite State Machines (FSMs) in a visual programming game based on flowcharts, aimed at enhancing the learning experience of programming concepts. Traditional programming education methods often struggle to engage beginners, leading to the development of interactive and intuitive approaches such as visual programming games. In this context, FSMs are integrated to manage the behavior of game units, allowing for dynamic state transitions based on user-defined flowcharts. The research adopts the Game Development Life Cycle (GDLC) approach, focusing on initialization, pre-production, production, and alpha testing stages. The primary objective is to implement and validate the FSM's effectiveness in controlling unit behavior within the game. Users can design strategies through a drag-and-drop interface, creating flowcharts that translate into FSM models, which dynamically control unit actions during gameplay. Results from the alpha testing indicate that the FSM implementation successfully manages the transitions and behaviors of game units according to the conditions specified in the flowcharts. This demonstrates the technical feasibility and effectiveness of the approach. Although the study does not extend to beta testing and release stages, the alpha testing provides a solid foundation for future research and development focused on user experience and broader feedback.